Influence of obesity on serum levels of thyroid hormones among Indian adult population - Bhandari, Vinod; Kosta, Susmit; Bhandari, Mahak; Behl, Simran (International Journal of Research in Medical Sciences, 2020)
Background: Obesity and thyroid dysfunction are two most common clinical conditions that have been linked together closely in adult. The link has become more relevant in the context of an unprecedented rise in the prevalence of obesity worldwide. Obesity is normally observed by patients as being secondary dysfunction on serum levels of thyroid hormones. Objective: The Purpose of this study to assess serum thyroid hormones levels (fT3, fT4, TSH) variation in patients with obesity and normal thyroid function among Indian adults and to correlate serum levels of thyroid hormones with their classes of Body Mass Index (BMI). Methods: Authors performed a retrospective study of adult patients who were examined and analyzed serum levels of thyroid hormones at authors centre between February 2018 to November 2019. Results: A total of 231 adult patients were included. 122(52.8%) were males, mean age was 35.4±10.4 and mean BMI 34.2±5.8 respectively. Obesity was found higher in female 58(53.2%) than male 37(30.3%) participants (p<0.001), respectively. The mean TSH serum levels were significantly increased with increased BMI (2.04±1.19,2.51±1.22 and 3.39±1.19; p=<0.001). No association was found of serum fT4 (p=0.227) and serum fT3 (p=0.063) with BMI. Conclusions: Mean TSH serum levels showed a significantly increased with increased BMI. BMI was negatively associated with serum fT4 but had no association with serum fT3.